The Effect of Inflation and Economic Growth on Unemployment Rate in Asean Countries - Nindi Septrila; Erni Panca Kurniasih (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
This study aims to examine and analyze the effect of inflation and economic growth on the unemployment rate in ASEAN countries in 2010 – 2019. The form of this research uses a quantitative approach. The data used in this research is secondary data. The type of data used is sourced from the World Bank. The analytical method and tool used is the dynamic panel data regression method and the software used is Stata 13. The results of this study indicate that inflation in the short term and long term has a negative and insignificant effect on unemployment rates in ASEAN countries and economic growth in the short term has a negative and insignificant effect on the unemployment rate in ASEAN countries. negative and insignificant to the unemployment rate in ASEAN countries.